Siber urbanisme: Pemikiran Melayu tentang bandar pintar - Jalaluddin Abdul Malek, (Universiti Kebangsaan Malaysia, 2008)
Malays have since the Malacca Malay Sultanate been exposed to urbanization. But, they were marginalized under a “divide and rule” policy during colonial period. Only after gaining independence did they once again settle in urban areas through rural-urban migration under New Economic Policy (1971-1990), National Economic Growth Policy (1991-2000) and now National Visionary Growth Policy (2001-2010). Middle class Malays have thus grown in size in cities that are known as smart cities, cybercities, virtual cities and technopolis cities. Putrajaya and Cyberjaya are two such examples of intelligent cities with majority of the population comprising of Malays. There is a corresponding change in the Malay’s way of thinking from that of urbanism to cyberurbanism. This is in line with the development of intelligent cities and their increasing knowledge of Information Communication Technologies (ICTs)